(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Today’s modern communication requires high data transmission rate and low power consumption. One of the most common concept of data transmission can be achieved by Multiplexers. The Multiplexers are the logic designs where data can be transmitted by n number of inputs over transmission path based on the selection line producing the single input. The application of Multipis more active in communications system. AlsoLow power consumption and high-speed result is the major concern for choosing the digital circuits [1,2]. Here we designed 2:1 Multiplexer using CMOS technology with 45nm, 90nm, 180nm. Since CMOS offers less power consumption, we can till reduce the power consumed by using power reduction techniques. In this paper we designed and compared the 2:1 Multiplexer using Lector, LCnmos and LCpmos power reduction techniques.